The Implementation of Restorative Justice for the Criminal Action of Accident against Child Based On Regulation of the State Police of the Republic Of Indonesia Number 8 Year 2021 - Rahul Rahul Ardian Fikri (LEGAL BRIEF, 2021)
The application of restorative justice emphasizes on restoring the situation and restoring the balance of society and involving the community in recovery efforts. The study aims to determine the restorative application of the crime of child sexual intercourse at the Langkat Police, and the recovery of victims of sexual intercourse with children..by using empirical normative legal research methods, namely the amalgamation of normative legal approaches with the addition of various empirical elements to study and examine the application of legal norms that should be in accordance with the rule of law, referring to the law and supported by field research at the Langkat Police to obtain data on restorative applications by emphasizing the recovery of victims due to criminal acts. The results of research on the crime of sexual intercourse with children, by strengthening religious knowledge, and the role of parents should pay more attention to their children and a good environment in order to shape the child's character better